2007
DOI: 10.1007/s00405-007-0394-x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of transketolase TKTL1 is associated with shorter survival in laryngeal squamous cell carcinomas

Abstract: Tumorigenesis involves energy production by aerobic glycolysis ("Warburg effect") in malignant tumors. One of the key enzymes is transketolase. Transketolase, transketolase-like-1 (TKTL1), and transketolase-like-2 are known. Antibodies against TKTL1 exist for immunohistochemical investigations. This study investigated the influence of TKTL1 on survival and metastasizing in 40 laryngeal squamous cell carcinomas (SCCs, T2-T4, 27 metastasized). Staining was assessed by an immunoreactive score (IRS) with values fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…The expression of TKTL-1 in CGTH-W-1 and FTC 238 cells, which are supposed to be invasive because they are derived from metastases, was less pronounced. This is in line with immunohistochemical detections in laryngeal squamous carcinoma [4] where poorly differentiated and more advanced lesions showed higher staining intensities with anti-TKTL-1 antibody but no difference in the expression between metastasized and non-metastasized tumors was recorded. It has to be noted that cell lines can not reflect the situation in the tumor as a whole because TKTL-1 expression differs markedly between tumor cells in a given tumor [15] and the cell line investigated may have been derived from a low expressing cell of the tumor.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The expression of TKTL-1 in CGTH-W-1 and FTC 238 cells, which are supposed to be invasive because they are derived from metastases, was less pronounced. This is in line with immunohistochemical detections in laryngeal squamous carcinoma [4] where poorly differentiated and more advanced lesions showed higher staining intensities with anti-TKTL-1 antibody but no difference in the expression between metastasized and non-metastasized tumors was recorded. It has to be noted that cell lines can not reflect the situation in the tumor as a whole because TKTL-1 expression differs markedly between tumor cells in a given tumor [15] and the cell line investigated may have been derived from a low expressing cell of the tumor.…”
Section: Discussionsupporting
confidence: 89%
“…As also differentiated and anaplastic thyroid carcinoma show over-expression, inhibitors of this enzyme [3] may increase the efficacy of differentiating substances. High levels of TKTL-1 are correlated with invasion and poor prognosis in colonic, urothelial, laryngeal squamous and breast carcinoma [3][4][5]. Transketolase is a key enzyme in the non-oxidative part of the pentosephosphate-pathway and inhibition of this enzyme is expected to decrease the amount of ribose-5-phosphate and of NADPH, which are needed for nucleic acid synthesis and the synthesis of biomolecules especially of fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…These data are in line with previously published studies reporting that TKTL1 expression correlates with prognosis in patients with epithelial malignancies such as invasive colonic, urothelial, laryngeal, and ovarian cancers. 13,14,19 Furthermore, TKTL1 levels in breast cancer correlated significantly with Her2/neu overexpression, a marker for poor prognosis. 11 In adrenal malignancies, however, TKTL1 was not a predictor of outcome and it was also found in benign adrenal tumors and normal adrenal tissue.…”
Section: Discussionmentioning
confidence: 97%
“…Omissions in this communication, however, prevent an objective evaluation of this interpretation. Nevertheless, several studies using the antibody clone JFC12T10 in other tumor entities also reported an unfavorable prognostic significance of increased expression of TKTL-1 (2,4,5). In the present study, the importance of TKTL-1 for malignant tumor cells has been evaluated on the basis of our own experimental data.…”
Section: Introductionmentioning
confidence: 91%